Mensur Şehname tercümesi 41a- 80b - Şahin Demirel, Sema (My University, 2001)
TEZ ÖZETİ Eser, İstanbul Üniversitesi Merkez Kütüphanesi 6131 demirbaş numarasıyla kayıtlıdır. Üç cilt halinde ve tamamı 1778 varaktır. Ayrıca eserde minyatürlere yer verilmiş, her sayfası 25 satır olarak düzenlenmiştir. Üzerinde çalışılan 1. cildin boyu 39, eni 24.5, kalınlığı 7.5 cm'dir. Eser hicrî 1187, milâdî 1773 yılında tamamlanmıştır, kelime kelime bir tercüme değildir. Tez yazmanın 41a-80b varaklarını kapsamaktadır. 01b-40b varakları Sadettin ŞAHİN tarafından olarak hazırlanmıştır. Bu tezi hazırlamaktaki amaç Şehnâme'nin bu mensur tercümesini tanıtmaktır. Tez üç bölümden oluşmaktadır: Giriş, metin ve sözlük. Giriş kısmında Firdevsî, Şehnâme, Şehnâme çevirileri ve üzerinde çalışılan yazmayla ilgili bilgiler verilmektedir. Metin kısmında sayfa ve satır numaraları belirtilmiş, günümüz noktalama işaretlerine göre düzenlenmiş ve gerekli kısımlarda paragraflar yapılmıştır. Böylece eserden faydalanılması daha kolay hale getirilmek istenmiştir. Sözlük ise; hem alfabetik hem de kök esasına dayalı bir sözlüktür. Madde başı olarak kabul edilen kelimelerin altına o kelimeyle ilgili ara madde, deyim ve birleşikler sıralanmış, madde başı veya ara maddelerin ikinci, üçüncü unsur olarak geçtiği maddelere (g) işareti ile göndermeler yapılmıştır.

OF THESIS The book is registered under fixture number 6131 at the Central Library of Istanbul University. It is composed of 3 volumes with total pages of 1778. Also miniatures have taken place in the book with each page designed 25 lines. The length of the first volume on which work is being carried on, is 39 cm, width is 24.5 cm and thickness is based 7.5 cm. The work was completed on 1187 (date based on Hegira) or 1773 (date based on birth of Christ/ Christian era). It is not a translation word by word. The thesis covers pages 41a - 80b of the manuscript. Pages 01b - 40b have been prepared as a master's thesis by Sadettin ŞAHİN. The reason to prepare this thesis is to recognise the translation of ŞEHNAME in prose. The thesis is composed of three sections which are the introduction, the text and the dictionary. The introduction section gives information about Firdevsi, Şehname, Şehname translations and hand prints/ paints on which work is carried on. The text shows the pages and line numbers and designed according to punctuation marks used up to date and paragraps have been created at the necessary parts. This way, it has been aimed to get benefit of the work more easily. The dictionary is based on alphabetic and root principles. The wording accepted as the beginning (main) item has down below the intermediary item, expression and composed wording related to that word. The items identified as second, third factors of the main or intermediary items have been referred with marking ( ® ).
Keywords: Edebiyat; İran edebiyatı; İran Edebiyatı_Şehname; Şehname (Divan edebiyatı); Türk Dili